Assessment of the structural performance of corrosion-affected RC members based on experimental study and probabilistic modeling. (15th November 2016) - Lim, Sopokhem; Akiyama, Mitsuyoshi; Frangopol, Dan M.
Highlights: The steel weight loss along rebars is estimated by X-ray and digital image processing techniques. The effects of spatial variability of steel corrosion on the structural behavior of corroded RC beams are investigated. The relationship between Gumbel distribution parameters and corrosion amounts is developed for modeling steel corrosion. The effects of non-uniform and uniform steel cross-section models on the accuracy of finite element results are studied. Abstract: The severity of damage due to corrosion on reinforced concrete (RC) structures primarily depends on the magnitude and location of the steel corrosion. A finite element (FE) method has been used to evaluate the structural performance of RC members subjected to reinforcement corrosion. However, the difficulty in quantifying the residual rebar cross-sections in the concrete has been reported as the primary challenge in providing important parameters for modeling the corrosion damages on the steel reinforcement and concrete. The three primary objectives of this paper are to (a) experimentally investigate the effects of the spatial variability in the steel corrosion on the structural behaviors of five corroded RC beams, (b) establish a FE method to assess their deteriorated structural performances, and (c) develop Gumbel distribution parameters to estimate the spatial variability of corrosion for the rebars. In the experimental study, the spatial variability in the steel weight loss along the corroded rebars in the concrete medium was quantified using X-ray and digital image processing techniques. For the FE analysis, the experimental steel weight loss data was used for modeling the residual steel cross-sections, reduced concrete strength, and deteriorated bond interface. The flexural capacity obtained from the simulated beams is in agreement with experimental results.